Active control of cavity buffeting noise using a dielectric barrier discharge plasma actuator - Hu, Xingjun; Liang, Hongyang; Zhang, Yanghui; Wang, Jingyu; Guo, Peng (Mechanical systems and signal processing, 2024)
This work examines the active control of vehicle buffeting noise using a dielectric barrier discharge plasma actuator (DBD-PA). First, the buffeting noise characteristics of a cavity under different inflow wind speeds are established through a wind tunnel test, and the effectiveness of the buffeting noise measurement results is verified. Various types of actuator layouts are designed based on specific combinations of parameters, and the interval optimization algorithm is used to identify the layout type of actuators that have the best equalization control effect under different inflow wind speeds. The experimental results regarding buffeting noise characteristics show that the buffeting frequency and the peak value of the sound pressure level increase with the increasing of wind speed. The control results show that the overall control effect of the reverse layout of the span-wise DBD-PA (SDBD-PA) is better than that of the positive layout. Consequently, the control effects of the SDBD-PA layout decrease in the front, rear, and oblique directions. A DBD vortex generator (DBD-VG) has no control effect when it is arranged in the front but has a certain control effect when it is arranged in the rear. The control effect is better with longer DBD-VGs. The results of running the interval optimization algorithm at different incoming wind speeds are as follows: reverse-front-SDBD-PA and long-rear-DBD-VG can achieve the best equalization control effect of cavity buffeting noise. The average noise reduction values are 5.26 dB and 4.42 dB, respectively, and the maximum noise reduction values are 7.48 dB and 5.79 dB, respectively.